FROM CHILDHOOD WOUNDS TO HEALERS: UNDERSTANDING CHILDHOOD ADVERSITY AND PARENTAL ALCOHOLISM IN INDIA, A CROSS-SECTIONAL STUDY - Jayamohan, Anusree; Tomar, Shashi Prabha; Verma, Prashant (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2025)
Background: Traumatic incidents that happen before the age of eighteen, such as domestic abuse, violence, and child abuse, are known as adverse childhood experiences (ACEs). Unfortunately, the trend is on the increase globally. Long-term health problems like alcoholism, depression, and chronic illnesses can be brought on by these experiences. Girls are impacted differently by gender norms and conceptions, and adolescents affected by ACEs are more likely to experience health disparities. Purpose: The current study is undertaken to estimate the prevalence and frequency of various types of ACEs among medical students in Jabalpur, Madhya Pradesh. Methods: A cross-sectional study, 211 NSCB Medical College students' data were gathered with the use of the